Palynological study of carbonated mounds during the Holocene along the Atlantic and Mediterranean Moroccan margins - Rachid, Jihad; Hssaida, Touria; Hamoumi, Naima; Terhzaz, Loubna; Spezzaferri, Silvia; Frank, Norbert; Daghor, Lamia (Review of palaeobotany and palynology, 2020)
A palynological study of carbonate mounds of Atlantic and Mediterranean Moroccan margins was conducted on sediment boxcores MD13-3441, MD13-3456, MD13-3461, MD13-3465, MD13-3468 collected during the oceanographic cruise MD 194/Eurofleet - GATEWAY, which took place on June 2013. The organic remaining revealed a dominance of dinoflagellate cysts over the continental fraction, which showed very low rates. The use of pollen data, despite their low representativity, is proving to be a valuable tool for the paleoclimate interpretation. The palynological quantitative and qualitative analysis revealed the evolution of the paleoenvironment and climate change of the carbonate mounds during this study interval. The terminal Pleistocene-basal Holocene passage highlighted by the dominance of cold taxa of dinoflagellate cysts. The presence and dominance of tree and shrub pollen coupled by the presence of altitudinal conifers confirmed a cold climate in both continental and marine environments. During the lower-middle Holocene, the variations in the relative frequencies of dinoflagellate cyst associations reflect the evolution of the paleoenvironment from inner neritic to oceanic. The recorded microflora shows a cyclicity during the lower Holocene from arid to semi-arid between 10.07 and 9.85 ka (the abundance of herbaceous and steppe), to become arid again around (9.69 ka) by the consistently high rate of herbaceous and steppe. In contrast, the paleoclimate recorded during the Middle Holocene is semi-humid to 6.29 ka (high rate of trees and shrubs) and evolves to a warm dry climate at 5.9-5.14 ka, reflected by the abundance of herbaceous and steppe.